Rejoinder - Toby C. Monsod; Aleli D. Kraft; Cielo Magno; J. C. Punongbayan; Orville Jose C. Solon; Elizabeth Tan; Agustin L. Arcenas; Florian A. Alburo; Emmanuel S. de Dios (University of the Philippines, School of Economics (UPSE), 2024)
We are pleased to note that the discussion paper we wrote ("How to change a constitution by handwaving") has attracted some interest from the public and observers of economic policy. Among the more thoughtful responses the paper has received is that from the Foundation for Economic Freedom (FEF). Indeed, their response concedes the main point of our paper, which is that compared with lifting foreign-equity restrictions: "Corruption and infrastructure gaps may well be more significant turnoffs for foreign investors." Notwithstanding this, the FEF response incongruously then insists that "removing the restrictions is a necessary condition". To insist on their conclusion, the FEF challenges our interpretation of the quantitative evidence as well as presents illustrative anecdotes or events meant to repair what they perceive as our paper's being "ahistorical and devoid of historical context". Here, we set the record straight on both FEF's appreciation of the econometric evidence and on the anecdotes they recount.
Keywords: 330